Genetic heterogeneity, evolution and recombination in emerging G9 rotaviruses - Tung Gia Phan (2018)
G9 rotavirus is recognized as the emerging genotype spreading around the world. The rapidly increasing detection of this virus in association with the genetic heterogeneity raises questions regarding its origin and epidemiological importance. A total of 380 sequences of rotavirus G9 strains including our sequence data from Vietnam and Japan, which were detected from 1983 to 2006 in five different continents, were collected from GenBank to investigate their heterogeneity and evolution. A novel nomenclature for G9 rotaviruses is proposed, in which these viruses are clustered into 6 lineages with 11 sublineages. Multiple amino acid substitutions of VP7 specific for lineages and sublineages were found. Interestingly, six short amino acid motifs correctly defined phylogenetic lineages and sublineages. Another interesting finding was the identification of recombinant G9 rotavirus, bearing different genotype sequence. In view of rotavirus evolution, this report is an additional evidence to support the notion that there might exist a genomic relatedness between human and porcine rotaviruses. © 2007 Elsevier B.V. All rights reserved.